R&D approach based on multiple partners and Design Thinking, Lean Startup, and Agile concepts: A case study in the electricity sector - Leal, Lorenna Fernandes (2021)
Goal: The paper aims to increase the understanding of the results and challenges that arise when running R&D projects based on multiple partners and the integration of Design Thinking, Lean Startup, and Agile concepts. Design / Methodology / Approach: We followed a case study approach in the electricity sector. Two project cases were studied, using triangulated data from interviews, internal documents, and non-participant observations. Results: The results of the Design Thinking, Lean Startup, and Agile concepts application in R&D projects show improvements in knowledge absorption, solution improvement through collaborative insights between partners, and identification of short-term opportunities. Some challenges, however, were identified, such as noisy integration, the role of the project manager requiring a sophisticated skillset, and complicated decision-making processes. Limitations of the investigation: The conclusions have the inherent limitations of a case study conducted in one industrial sector and two projects led by one company. Practical implications: The evolving competitive landscape demands more effective pathways to foster innovation. Recent approaches to innovation have challenged R&D practices. This study discusses a new way of addressing R&D efforts with multiple partners by integrating Design Thinking, Lean Startup, and Agile concepts. Originality / Value: The combined and coherent application of concepts derived from Design Thinking, Lean Startup, and Agile in R&D practices in the electricity sector is new. The high volume of R&D activity in the electricity sector makes this in-depth analysis both relevant and valuable.